STUDI TENTANG MOTIVASI DAN KARAKTERISTIK PRIBADI KARYAWAN SARI SEHAT HERBAL MEDICINE INDUSTRY di MAGELANG - Yan Kurnia Putri (JURNAL MANAJEMEN, 2014)
This study aims to examine and analyze the influence of personal characteristics on employee motivation Sari Sehat Herbal Medicine Industry and to determine whether the employee motivation Sari Sehat Herbal Medicine Industry in Magelang . Data collected through questionnaires and conducted on 89 employees Sari Sehat Herbal Medicine Industry Magelang . Analysis of the data in this study using SPSS version 17 . In this study used a sample of the entire population and data testing techniques used in this study include test validity , reliability tests with Cronbach alpha . Spearman correlation analysis to examine the relationship between personal characteristics such as age , education , length of employment , marital status of the motivation , by comparing the value Sig.ρhitung with α value ( 0.05 ) . As for analyzing gender relations to motivation chi square analysis was used to compare the value of Sig . χ ^ 2hitung the value of α ( 0.05 ) . The analysis showed that the level of personal characteristics ( 0.003 ) , length of employment ( 0 ) and marital status ( 0.006 ) effect on employee performance . Age (0.524 ) and gender (0.217 ) had no effect on motivation . And the biggest motivation for employees Sari Sehat Herbal Medicine Industry is salary ( 79 % ) . This research